Design and Development of Unmanned Grass Cutter - Sivarao, Subramonian (LA Publishing, 2010)
Unmanned Grass Cutter The traditional ways of grass cutting for wider fields using manually operated machines requires full time highly skilled labor. Furthermore, there can be labor-imposed constraints which limits the use of these machines in hot sun or heavy down-pour. Therefore, a common tractor which normally used for grass cutting has been modified to be a semi automatic grass cutter. This machine requires no operator during the entire grass cutting operation, except for initiating and stopping the machine at initial and eventual stages. The spiral way of grass cutting can be tuned to be double cutting so that the machine cuts the grass twice for better trimming of the grass height. A simple mechanism is attached to the modified steering wheel in order to gain the benefits of automatic grass cutting.